Administrative Clemency and Legal Correction in Article 36 Of the UU KUP: A Proposal for Normative Redesign - Adriana Dwi Hardjanti; Marhaeni Ria Siombo (International Journal of Social Service and Research, 2026)
Article 36 of Indonesia’s Law on General Provisions and Tax Procedures (UU KUP) serves as an important mechanism for addressing administrative sanctions, material errors, and procedural defects in tax administration. However, the provision applies a uniform discretionary formulation through the term “may” to fundamentally different forms of authority, creating ambiguity between administrative clemency and legality-based correction. This design has raised concerns regarding legal certainty, taxpayer protection, and the consistency of administrative decision-making. Therefore, this study aims to analyze the substantive characteristics of Article 36 paragraph (1) and evaluate the compatibility of its discretionary formulation with the principles of legality, legal certainty, and administrative justice. This research employed a normative juridical method using statutory and conceptual approaches. Primary legal materials consist of relevant legislation and Constitutional Court decisions, while secondary materials include scholarly books and journal articles on tax law and administrative law. Data were analyzed qualitatively through descriptive, analytical, and prescriptive legal reasoning. The findings reveal an ontological dualism within Article 36, where administrative clemency and legality-based correction are regulated under a single discretionary framework despite their distinct legal characteristics. While administrative clemency appropriately involves discretion, the correction of material inaccuracies and serious procedural defects constitutes a legal obligation that should be treated as bound authority. The study proposes a normative redesign separating these domains and transforming legality-based correction into an imperative duty. Such reconstruction enhances legal certainty, strengthens taxpayer protection, improves judicial review, and reinforces the rule of law within Indonesia’s tax administration system.